Social Constructions of Deafness : Examining Deaf Languacultures in Education - Horejes, Thomas P. (Book collections on Project MUSE., 2012)
"Thomas P. Horejes's new book focuses on revealing critical knowledge that addresses certain social justice issues, including deafness, language, culture, and deaf education. He conveys this information through discourses about his own experiences being deaf and through his research in which he "stresses the contingency of the social" in educational institutions. In Social Constructions of Deafness: Examining Deaf Languacultures in Education, Horejes contends that schools as social institutions play powerful and exacting roles in the creation and maintenance of social constructions such as language and culture for deaf children. He subscribes to Michael Agar's concept of "lauguaculture," defined as the inextricable relationship between language and culture in which a specific language will shape and influence culture. His approach employs other anthropological terminology as he connects his personal experience as a deaf student (emic) to academic research on deafness (etic) to bring understanding to the multidimensional aspects of his own negotiated identities. Horejes extends his inquiry through his analysis of two kindergarten classes for deaf students, one orally oriented and the other conducted using sing language. His findings are sobering evidence of the myriad challenges educators face in defining appropriate academic, linguistic, and cultural pedagogy for deaf children in schools and other social institutions."--Books.google.